Implementasi Kebijakan Online Single Submission Risk Based Approach (Oss Rba) di Kecamatan Kalidoni Kota Palembang - Liatosa Yundrina (Journal on Education, 2023)
The concept of good governance today is starting to influence most government stakeholders at the central and regional levels, the impact of which is to foster a spirit of improving and enhancing the performance of government management to improve the quality of public services, and to translate it into various regional government policies. The purpose of this study was to find out and explain the implementation of the Online Single Submission Risk-Based Approach policy in Kalidoni District, Palembang City. Realizing it or not, every citizen is always associated with the activities of the government bureaucracy, so that its existence is something that cannot be negotiated. The research method used in this study is a qualitative descriptive research method. Acceleration of the implementation of OSS RBA in the regions requires the support of certainty and completeness of Central digital policies and systems. Incomplete regulatory substance in a number of PPs, technical provisions have not yet been issued (which are still delegated to ministerial regulations), and the integration process between systems is not yet optimal, which is an obstacle for regions to follow up and implement OSS RBA quickly. Meanwhile at the regional level, regional governments face a number of challenges, both in regulatory and institutional aspects, as well as digitalization.